Sports and health tourism as a means maintaining students’ health - Hrohova, G. P. (Problems of Engineer-Pedagogical Education, 2018)
The article proves that maintaining health is one of the primary objectives whose accomplishment requires a balanced approach to all spheres of human activity. It has been confirmed that recreational activities of sports and health tourism can be distinguished among the above-stated approaches, as nowadays hey are regarded as one of the most effective aspects of preserving health, healthy lifestyle of every individual in particular and society in general being of great national importance. It is evident that the organization of tours for students is extremely demanding. The process of providing such services is highly problematic for travel agencies, since in order to benefit from it economically, one needs to invest a lot more than in the organization of tours for adults. The positive impact of tourism occupation is definitely aggravated by the long motor activity of staying in the fresh air, in the forest, in the mountains, and hiking trips with an impact on the whole body is a healing source of health. Preserving the health of student youth is done by changing the type of activity and metered physical activity by interaction with the natural environment during the whole trip or hike, excursion or walks, health-improvement or sports-tourist activities.